1998
DOI: 10.1530/eje.0.1380322
|View full text |Cite
|
Sign up to set email alerts
|

Changes in carbohydrate metabolism of testicular germ cells during meiosis in the rat

Abstract: A study was undertaken to estimate the activities of the key enzymes of glycolysis, the pentose phosphate pathway and the tricarboxylic acid (TCA) cycle in purified rat spermatocytes and spermatids, which have been shown to die in glucose-containing medium and require lactate/pyruvate for maintaining normal ATP concentrations. The aim was to elucidate the changes in the glycolytic and oxidative potential of germ cells undergoing meiosis. Pachytene spermatocytes and round spermatids from adult rat testis were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 22 publications
3
89
0
1
Order By: Relevance
“…Supportive of this notion is the demonstration that these other nondying cell types, such as Sertoli cells and spermatogonia, are known to use glycolysis for their energy production (whereas the dying cell types prefer OXPHOS; see Refs. 3,28,45,53,64). Of note, when using OXPHOS inhibitors, we cannot exclude the possibility that the ATP decrease would occur in different cells than the death process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supportive of this notion is the demonstration that these other nondying cell types, such as Sertoli cells and spermatogonia, are known to use glycolysis for their energy production (whereas the dying cell types prefer OXPHOS; see Refs. 3,28,45,53,64). Of note, when using OXPHOS inhibitors, we cannot exclude the possibility that the ATP decrease would occur in different cells than the death process.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogonia, mature spermatozoa, and the somatic Sertoli cells exhibit high glycolytic activity, whereas spermatocytes and spermatids produce ATP mainly by mitochondrial oxidative phosphorylation (OXPHOS; see Refs. 3,28,31,37,45,53,64). Interestingly, the cell types that use OXPHOS for energy production (i.e., spermatids and spermatocytes) are sensitive to death-inducing signals such as hormonal deprivation, Fas activation, and elevated temperature (19,24,34,47,48,51,60,60).…”
mentioning
confidence: 99%
“…From a nutrition perspective, glucose is known to play an important role in energy metabolism in the testis. Germ cells use glucose and lactate, which is converted from glucose and is supplied by Sertoli cells (Rato et al, 2012;Bajpai et al, 1998;Boussouar and Benahmed, 2004;Jutte et al, 1982;Robinson and Fritz, 1981). Nevertheless, there are few reports evaluating the effects of glucose deficiency (hypoglycemia) on the testis.…”
Section: Introductionmentioning
confidence: 99%
“…Rathi et al (2005) suggested that meiotic/post-meiotic cells may be less likely to survive the hypoxia associated with the procedure. This is logical given the requirements in rodents for oxidative metabolism as opposed to glycolysis in post-meiotic germ cells (Grootegoed et al 1986;Nakamura et al 1986;Bajpai et al 1998) and could account for the loss of differentiating male germ cells seen soon after placement of donor tissue containing meiotic cells. Yet, once having been lost, the underlying complement of SSC should, theoretically, have been the same as in prepubertal donors and, therefore, should still have been able to recover and repopulate to support spermatogenesis over the 50 week period.…”
Section: Discussionmentioning
confidence: 99%